Institutional characteristics, investment sensitivity to cash flow and Tobin's q: Evidence from the Middle East and North Africa region. (3rd January 2020) - Al‐Nasser Abdallah, Abed; Abdallah, Wissam; Saad, Mohsen
Abstract: We examine the sensitivity of corporate investment to stock‐market valuations (measured by Tobin's q ) and internal funds (measured by cash flow) in a setting that captures the unique country institutional characteristics of the Middle East and North Africa region. We report a higher sensitivity of investments to cash flow than Tobin's q . However, both sensitivities are unaffected by the country institutional characteristics. By examining the sensitivity of investments to cash flow and Tobin's q before and after the 2008 global financial crisis, we document that the investment‐cash flow relation has weakened over time, while the investment‐Tobin's q relation has significantly strengthened. Finally, after dividing our country sample into resource‐rich and resource‐poor countries, the importance of cash flow over Tobin's q in the determination of corporate investment levels is asserted and the role of financial markets is found to be restricted to resource‐rich countries only.